Development Of Digital Student Worksheet In History Subject For The Elevent Grade By Using ASSURE Model. - Siti Jumratul Aini; Mohamad Na'im; Kayan Swastika; Ahmad Ryan Pratama (History Education, University of Jember, 2020)
Developing of teaching materials that innovative, interesting, effective and it’s developed by advances technology into an obligation in order to be able to facilitate a good teaching. Therefore the educaters have the obligation to develop the teaching materials by herself or his self and must give a good teaching and effectively. The purpose of this research is to produce the product as LKPD effectively for Indonesian History subject to the elevent grade by using ASSURE model that is validated. This research subject is 32 social students of elevent grade in SMAN 5 Jember. This research is done in January 2018. It result shows that the product of validation teaching materials can measure the effectiveness level. In classic the validation result of the subject contain is amount 80 percents, the desaint validation is amount 88,4 percents, the media validation is amount 86 percents and the language validation is amount 94 percents. The effectiveness level of trial result in small group is amount 71,12 percents, while in large group is amount 86,75 percents. The conclution of this research is developing product in digital student worksheet use ASSURE model that validates by the experts and it can develop the Indonesian history teaching effectiveness. Keywords: Student Worksheets, ASSURE, Expert Validation, Effectiveness